Insect olfactory neurons in vitro: morphological and physiological characterization of cells from the developing antennal lobes of Manduca sexta - Hayashi, JH (J Neurosci, 1990)
To facilitate studies of the development and membrane biophysics of cells in the central olfactory pathway of the moth Manduca sexta, we have dissociated neurons and glial cells from the antennal lobes (ALs) and cultivated them in the controlled environment of tissue culture. Cultures produced from cells of the lateral group of AL neurons alone are enriched in local interneurons (LNs), while cultures made from cells of the median and anterior groups of AL neurons contain projection neurons (PNs) but lack LNs. Cultures containing only PNs, but not cultures with both PNs and LNs, require a conditioning factor derived from a conspecific cell line in order to ensure survival. Under these conditions, we identify 5 types of cells in the “PN-only” cultures that are consistently observed and distinguishable on the basis of their morphology and characteristic whole-cell current profiles. In cultures that contain both PNs and LNs, we find 3 additional types of cells with neuronlike appearance. Whereas the PNs have whole-cell currents that suggest a neuronal phenotype, we have not yet observed similar currents in the 3 other types of cells. We tentatively identify the latter 3 cell types as LNs whose development has been arrested. The conditioning factor also has a trophic effect on phase-dark, multipolar cells that are observed in freshly dispersed cultures. Their morphology and whole-cell currents lead us to suggest that they are glial cells.